Assessing Financial Performance Of State-Owned Holding Structures In Indonesia’s Mining Sector - susilo, florentinus suryo; Jaya, Wihana Kirana; pitoyo, agus joko; Noer Arfani, Riza (Accounting Department,, 2025)
Purpose —State-owned enterprises (SOEs) are crucial in economic development, particularly in strategic sectors. The state-owned holding (SOH) structure has been introduced as a governance model to enhance efficiency, reduce agency conflicts, and improve financial performance. Using financial data from 2017 to 2022, this study focuses on assessing the holding structures on the financial performance effectiveness of mining sector companies in Indonesia. Unlike prior studies that predominantly examine SOH models in advanced economies or through multinational SOEs, this research centres on a developing country context where SOEs play a pivotal role in industrial policy and national economic strategy. Design/methodology/approach —by using a quantitative approach from financial performance data of MIND ID as an Indonesian mining holding SOE, and also financial performance of Indonesian mining industries, this study assesses the holding structure, foreign ownership, and availability of independent directors to the financial performance. Findings—These findings can encourage companies to reflect on their ownership structure and consider changes to improve financial effectiveness, such as increasing the involvement of foreign investors or strengthening governance mechanisms. Practical implications — This study's findings provide practical implications by providing empirical references for investors to understand the risks and opportunities associated with ownership structure in the mining sector. Originality/value —. This paper presents the case of an SOE holding company in Indonesia's mining sector. It differs from some of the previous literature that generally studies more SOEs concerning governance.